Answer:
f(2) =5
Step-by-step explanation:
We have a function f(x) = 3x-1
When we find f(2) ,let x=2
f(2) = 3*2-1
= 6-1
=5
Answer: x = (cd + by) / a
Working out:
(ax - by) / c = d
1)Multiply by c on both sides to get:
ax - by = cd
2) Add by on both sides to get:
ax = cd + by
3) divide by a on both sides to get:
x = (cd + by) / a
2. I think the answer is 24
subracting the last 2 inequalities we get
6x + 7y <= 42
3x + 2y <= 18 subtract:_-
3x + 5y <= 24
Answer:
45 degrees
Step-by-step explanation:
Answer: 16
Step-by-step explanation: When you have a set of parentheses in an order of operations problem, you must simplify what's inside that set of parentheses first before you do anything else.
So our first step here is to subtract 6 - 8 which gives us -2.
So in our next step we have 3 (-2)² + 8 ÷ 2.
Now remember to do exponents before you multiply.
So (-2)² is just -2 × -2 or 4.
So in our next step we have 3 x 4 + 8 ÷ 2.
Now, we multiply so we have 3 x 4 which is 12.
So we have 12 + 8 ÷ 2.
Now we can divide.
8 ÷ 2 is 4 so we have 12 + 4 or 16.
So the answer to this problem is 16.